Involvement of neuronal β2 subunit‐containing nicotinic acetylcholine receptors in nicotine reward and withdrawal: Implications for pharmacotherapies. (14th May 2014) - Simmons, Steven J.; Gould, Thomas J.
Summary What is known and objective Tobacco smoking remains a major health problem. Nicotine binds to nicotinic acetylcholine receptors (nAChRs), which can cause addiction and withdrawal symptoms upon cessation of nicotine administration. Pharmacotherapies for nicotine addiction target brain alterations that underlie withdrawal symptoms. This review will delineate the involvement of the β2 subunit of neuronal nAChRs in nicotine reward and in generating withdrawal symptoms to better understand the efficacy of smoking cessation pharmacotherapies. Comment Chronic nicotine desensitizes and upregulates β2 subunit‐containing nAChRs, and the prolonged upregulation of receptors may underlie symptoms of withdrawal. Experimental research has demonstrated that the β2 subunit of neuronal nAChRs is necessary for generating nicotine reward and withdrawal symptoms. What is new and conclusion Smoking cessation pharmacotherapies act on β2 subunit‐containing nAChRs to reduce nicotine reward and withdrawal symptom severity.